Optimizing cryopreservation of sea cucumber (Apostichopus japonicus) sperm using a programmable freezer and computer-assisted sperm analysis - Xu, Shuai; Liu, Shilin; Sun, Jingchun; Zhang, Libin; Lin, Chenggang; Sun, Lina; Xing, Lili; Jiang, Chunxi; Yang, Hongsheng (Frontiers in Marine Science, 2022)
The sea cucumber Apostichopus japonicus has high nutritional, medicinal, and economic value. However, factors such as overexploitation, climate change, and environmental pollution have resulted in serious germplasm degradation in both farmed and wild A. japonicus, and it has been listed as endangered on the IUCN (International Union for Conservation of Nature) Red List of Threatened Species. Cryopreservation is an important method to protect germplasm resources and solve the problem of germplasm degradation. Using a programmable freezer and computer-aided sperm analysis, we comprehensively studied and screened the factors that affect the post-thaw motility of A. japonicus sperm during cryopreservation. Based on our results, we propose the following optimal cryopreservation procedure for A. japonicus sperm: cryo-diluent composition of 12.5% dimethyl sulfoxide and 0.1 mol/L glucose, with filter-sterilized (the filter mesh size: 0.45μm) natural seawater (NSW) as the extender; 1:5 mixing ratio of sperm and cryo-diluent; cooling rate and thawing temperatures of 10°C/min and 20°C, respectively. The post-thaw motility of sperm treated using the optimal procedure was > 65%, the fertilization rate (in the blastocyst stage) was nearly 80%, and the hatching rate (in the early auricularia larva stage) was > 65%. Additionally, frozen sperm that had been cryopreserved for 1 year retained a considerable post-thaw motility and fertilization rate compared to recently cryopreserved sperm. We detected obvious differences in sperm freezability among individual A. japonicus, and cryopreservation caused some damage to the sperm structure. In conclusion, our optimized procedure make large-scale cryopreservation of A. japonicus sperm possible, and our results provide valuable information that could be applied to research and conservation of A. japonicus.